Pattern of Cranio-Cerebral Injuries at a Tertiary Care Centre – A Retrospective Study - Anand Patil1, Tasgaonkar V N1, Rakesh M Marigoudar2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Head injuries are accounting for most serious injuries in terms of morbidity and mortality1. The present study was carried out at a tertiary care hospital, Maharashtra for duration of three years. This study was conducted on 173 cases, which were directly brought to mortuary for postmortem examination from the site of incidence. The objective of this study is to find out the pattern of skull fractures irrespective of cause of injury. Linear fracture was found to be more common among the total no of cases. In the present study it was observed that skull fractures are more commonly seen in assault cases. In this study it is observed that extradural hemorrhage is most commonly associated with motor cycle riders. It has been also noticed that younger age group (21-30 years) are most commonly effected age group. In this present study it is noticed that abrasions are the most common type of injuries associated with skull fractures.